A colonic amoebic abscess mimicking colonic carcinoma - Tan, Li Peng; Kan, Foong Kee; Lim, Yvonne Ai Lian (Malaysian Medical Association, 2018)
Amebiasis is one of the major causes of diarrhea in the developing countries and it can present with a wide range of gastrointestinal symptoms depending on the phase of infection. We described a case of 50 year-old male patient who presented with abdominal pain, diarrhea and vomiting. After right hemicolectomy for appendicular abscess with tumour over the ileum, histopathological examinations revealed numerous trophozoites of Entamoeba histolytica in a background of inflammations (Figure 1). Following resection of the ameboma, he received intravenous metronidazole treatment for total of two weeks duration.